2020
DOI: 10.5539/ibr.v13n3p68
|View full text |Cite
|
Sign up to set email alerts
|

Hotel-Related Factors and Employee Performance "The Case of Jordanian Four Star Hotels"

Abstract: The study addresses the challenge of employee performance (EP) at the four-star hotels in Jordan by focusing on how hotel-related factors influencing EP. Multiple regression was used to predict EP and explain the impact of five predictors that are organization culture (OC), organization structure (OS), manager attitude (MA), empowerment (EM), and training culture (TC). A correlation was used to compare the relationship between study variables. The results of multiple regression indicated that EM was the strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…** Accepted due to the high score of composite reliability (Fornell & Larcker, 1981). learning (Jeong et al, 2018;Zia et al, 2022) and less with training methods that favor formal learning (Nugroho, 2018;Alfandi, 2020). Analytically, it was found that the performance of a hotel's HR in this field is primarily related to the training method of the Case Study (Radi Afsouran et al, 2018) and secondary with the training methods of Business Games (Martin et al, 2014) and Lectures (Furunes, 2005).…”
Section: Exploratory Factor Analysis Resultsmentioning
confidence: 99%
“…** Accepted due to the high score of composite reliability (Fornell & Larcker, 1981). learning (Jeong et al, 2018;Zia et al, 2022) and less with training methods that favor formal learning (Nugroho, 2018;Alfandi, 2020). Analytically, it was found that the performance of a hotel's HR in this field is primarily related to the training method of the Case Study (Radi Afsouran et al, 2018) and secondary with the training methods of Business Games (Martin et al, 2014) and Lectures (Furunes, 2005).…”
Section: Exploratory Factor Analysis Resultsmentioning
confidence: 99%
“…Sustainability involves keeping the natural environment is not destroyed for present and future generations, and reducing the negative effect of enterprises on public health, social welfare, and economic growth, as well as implementing green innovation activities (Shabana, 2023). Sustainability refers to achieving long-term prosperity and involves all three of the following dimensions simultaneously: ecological, social, and economic (Alfandi, 2020). This is a comprehensive approach and is applicable in all sectors and for all sustainable development drivers of enterprises (Alfandi & Bataineh, 2023).…”
Section: Sustainable Performancementioning
confidence: 99%
“…Sustainability is an integrated approach that takes into account ecological, social, and economic elements that must be considered together to achieve long-term prosperity (Alfandi, 2020). It considers the working environment a success factor that should be combined with business processes (Ploum et al, 2018).…”
Section: Sustainable Performance (Sp)mentioning
confidence: 99%
“…It considers the working environment a success factor that should be combined with business processes (Ploum et al, 2018). In the tourism and hospitality industry, sustainability is any activity that continuously works to maintain and promote the environment, other natural resources, cultural values, and social justice (Alfandi, 2016).…”
Section: Sustainable Performance (Sp)mentioning
confidence: 99%